Urban planet : knowledge towards sustainable cities - Elmqvist, Thomas (Cambridge University Press, 2018)
Global urbanization promises better services, stronger economies, and more connections; it also carries risks and unforeseeable consequences. To deepen our understanding of this complex process and its importance for global sustainability, we need to build interdisciplinary knowledge around a systems approach. Urban Planet takes an integrative look at our urban environment, bringing together scholars from a diverse range of disciplines: from sociology and political science to evolutionary biology, geography, economics and engineering. It includes the perspectives of often neglected voices: architects, journalists, artists and activists. The book provides a much needed cross-scale perspective, connecting challenges and solutions on a local scale with drivers and policy frameworks on a regional and global scale. The authors argue that to overcome the major challenges we are facing, we must embark on a large-scale reinvention of how we live together, grounded in inclusiveness and sustainability. This title is also available Open Access.
Title from publisher's bibliographic system (viewed on 27 Apr 2018).
Keywords: Urbanization; City planning -- Environmental aspects; Sustainable development